Razumem zgodbo - razumem svet? - Nemec, Maja (Analiza (Ljubljana), 2025)
Contemporary debates in the analytical philosophy of fiction have revolved around the epistemic value of literary works. The article attempts to bridge the gap between optimistic literary cognitivists and sceptical anti-cognitivists by arguing that the epistemic contribution of literature lies more in understanding than in the search for bare facts. The basis for this is the distinction between propositional knowledge and understanding, which literary works enable even in non- realistic genres. Understanding will be treated as an independent epistemological concept, distinct from a type of knowledge. In doing so, I draw on contemporary neocognitivist approaches (Mikkonen, Ferran), which treat understanding as a central epistemic virtue, and on the critique of the aesthetic distinction between philosophy and literature (Vidmar Jovanović). The final section of the article considers aesthetic objections to cognitivism (as developed by Lamarque and Olsen), who argue that attributing epistemic value to fiction is trivial and potentially dangerous, as it risks reducing works of art to a purely didactic instrument. I attempt to demonstrate how fiction, through its aesthetic form and complexity, facilitates cognitive gains that extend beyond its didactic role.
Keywords: epistemic values; epistemska vrednost; fiction; fikcija; literarni kognitivizem; Literarno vrednotenje; literary cognitivism; propositional knowledge; propozicionalno vedenje; razumevanje; understanding